The Dominan Concept of Corporate Social Responsibility Projects Based on Bibliometric Analysis: Improving Quality or Stagnation? - Rahmah, Laily Ainur; Salahudin, Salahudin (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
Corporate Social Responsibility (CSR) has an important role in improving the company's existence. CSR was formed to implement empowerment to society, attract the attention of surrounding society and build the company's image. This paper aims to examine implementation of society empowerment through the CSR program. This study uses the method of study literature and bibliometric analysis by collecting previous research articles that are indexed in Scopus database and have correlation with CSR programs, which are then carried out using bibliometric analysis using the VOS viewer. This analysis makes it easier for the author to make a common thread about dominant concepts studied. This study reveals that society empowerment in an effort to improve economic level and welfare of society through CSR programs is able to increase the responsibility and quality of companies in Indonesia. Besides that, it also has an impact on the quality of the economy and helps society to face the dynamic economy, social and culture in the future. For further research, it is expected to pay attention to dominant concepts contained in CSR programs, especially in implementation of society development around the company as consideration for improvement and refinement of research to be carried out.